Moisture diffusivity in high oleic sunflower seeds and kernels - Santalla, Estela Mercedes (2010)
Moisture diffusivities in high oleic seeds and kernels were obtained from experimental thin layer drying rates in the range of 25–90°C air temperature and 4.2–33.5% initial moisture content (d.b.). Moisture diffusivity back-calculated from Fick´s second law of diffusion varied between 0.85.10-10 and 7.26.10−10 m2/s for seeds and between 0.37.10−10 and 2.39.10−10 m2/s for kernels. The Arrhenius activation energy for seeds and kernels resulted 31 and 24 kJ/mol, respectively. A new model based on the kinetic parameter of Page equation was proposed as a simple tool to predict water diffusion in high oleic sunflower seeds and kernelss.